Unsafe abortion: the silent scourge - Mallaiyan, Sharadha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Unsafe abortions continue to cause maternal morbidity and mortality in developing countries. The practice of unsafe abortions by quacks needs to be checked. Our study aims to emphasize upon the unmet needs of medical termination pregnancies (MTP) services in rural India and to recognize the complications due to it and the efficient management of such cases at tertiary care center. Methods: A two years retrospective study of septic abortions from December 2009 to November 2011. Results: Among 1080 abortions reported, 44 were septic-4.07%. More commonly in the age group of >20years (81.9%). 77.3% of them were multiparous and 22.7% were nulligravidae, with an increased incidence of unmarried nulliparous pregnancies. Greater numbers occurred during 1st trimester (77.2% versus 22.7%), with 54.5%-grade I, 29.5%-grade II, 15.9% grade III in severity. Majority of cases were due to evacuation by quacks (72.7%). Among the 44 cases, emergency laparotomy was done for 5 cases of grade III severity. The mortality rates due to septic abortion were 6.25% (3) among the total of 48 maternal deaths. Conclusions: Septic abortion is totally preventable. Majority of uneducated rural women are not aware of MTP services. The reproductive and child health (RCH) services should effectively reach the underprivileged population like slum dwellers and migrants.